Role of sodium-dependent vitamin C transporter-2 and ascorbate in regulating the hypoxic pathway in cultured glioblastoma cells - Burgess, Eleanor R.; Praditi, Citra; Phillips, Elisabeth; Vissers, Margreet C. M.; Robinson, Bridget A.; Dachs, Gabi U.; Wiggins, George A. R. (Journal of cellular biochemistry, 2024)
The most common and aggressive brain cancer, glioblastoma, is characterized by hypoxia and poor survival. The pro-tumour transcription factor, hypoxia-inducible factor (HIF), is regulated via HIF-hydroxylases that require ascorbate as cofactor. Decreased HIF-hydroxylase activity triggers the hypoxic pathway driving cancer progression. Tissue ascorbate accumulates via the sodium-dependent vitamin C transporter-2 (SVCT2). We hypothesize that glioblastoma cells rely on SVCT2 for ascorbate accumulation, and that knockout of this transporter would disrupt the regulation of the hypoxic pathway by ascorbate. Ascorbate uptake was measured in glioblastoma cell lines (U87MG, U251MG, T98G) by high-performance liquid chromatography. CRISPR/Cas9 was used to knockout SVCT2. Cells were treated with cobalt chloride, desferrioxamine or 5% oxygen, with/without ascorbate, and key hypoxic pathway proteins were measured using Western blot analysis. Ascorbate uptake was cell line dependent, ranging from 1.7 to 11.0 nmol/106 cells. SVCT2-knockout cells accumulated 90%-95% less intracellular ascorbate than parental cells. The hypoxic pathway was induced by all three stimuli, and ascorbate reduced this induction. In the SVCT2-knockout cells, ascorbate had limited effect on the hypoxic pathway. This study verifies that intracellular ascorbate is required to suppress the hypoxic pathway. As patient survival is related to an activated hypoxic pathway, increasing intra-tumoral ascorbate may be of clinical interest.
Erstmals veröffentlicht: 09. Oktober 2024
Gesehen am 07.01.2025